Malfunctioning of the Public Distribution System: An Empirical Analysis - Abraham Koshy (Vikalpa, 1991)
Public distribution system (PDS), which acquired prominence in India during the Second World War period, has evolved over the years as a major policy instrument of the government to ameliorate difficulties caused by shortages and price increases of foodgrains and other essential items. The commodities supplied at subsidized prices through PDS are aimed to benefit the more vulnerable sections of the society. Questions, however, have been raised about the effectiveness and efficiency of PDS in achieving its objectives which assume more importance because of the large quantum of subsidy involved. This article by Abraham Koshy focuses on one of the major concerns raised about the efficiency of PDS, namely, the extent of stock diversion at the retail points. This study was carried out in Kerala where PDS is perceived to be well developed and, therefore, the findings could be considered as a pointer towards the state of PDS operations in other states where it is less developed